Wood vinegar as a natural alternative to antibiotics: Effects on cecal microbiota, antioxidant status, and nutrient digestibility in broiler chickens - Sola Samson Emmanuel; Teck Chwen Loh; Hooi Ling Foo; Henny Akit; Muhamad Faris Ab Aziz; Eric Lim Teik Chung (Veterinary World)
Background and Aim: Antibiotic resistance has spurred interest in alternative feed additives for poultry. Wood vinegar (WV), a by-product of plant pyrolysis, contains bioactive compounds with antioxidant and antimicrobial properties. This study aimed to evaluate the effects of WV supplementation through drinking water on the cecal microbial population, volatile fatty acid (VFA) concentrations, antioxidant enzyme activity, and apparent ileal nutrient digestibility in broiler chickens.